2023
DOI: 10.3390/microorganisms11061570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agave Fructans on Changes in Chemistry, Morphology and Composition in the Biomass Growth of Milk Kefir Grains

Abstract: Prebiotic effects have been attributed to agave fructans through bacterial and yeast fermentations, but there are few reports on their use as raw materials of a carbon source. Kefir milk is a fermented drink with lactic acid bacteria and yeast that coexist in a symbiotic association. During fermentation, these microorganisms mainly consume lactose and produce a polymeric matrix called kefiran, which is an exopolysaccharide composed mainly of water-soluble glucogalactan, suitable for the development of bio-degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Such activation was revealed through flow cytometry, and it was observed that the detected effects depended on the kind of probiotic used and on the strain of E. coli used. The effect of agave fructans on chemical and morphometric characteristics of kefir grains [2]. The amount of inoculum and fermentation at 25 • C were the best for production, and it was noted that the addition of agave fructans in the medium promoted the production of biomass with respect to the lactose-free culture medium.…”
mentioning
confidence: 99%
“…Such activation was revealed through flow cytometry, and it was observed that the detected effects depended on the kind of probiotic used and on the strain of E. coli used. The effect of agave fructans on chemical and morphometric characteristics of kefir grains [2]. The amount of inoculum and fermentation at 25 • C were the best for production, and it was noted that the addition of agave fructans in the medium promoted the production of biomass with respect to the lactose-free culture medium.…”
mentioning
confidence: 99%